SEXIST HUMOR AS A FORM OF SEXUAL VIOLENCE AND PREVENTION EFFORT FROM AN ISLAMIC PERSPECTIVE - Aprianti, Reza; Ginting, Eraskaita (Psikis : Jurnal Psikologi Islami, 2022)
The emergence of several phenomena of sexual violence on television media between lecturers and students raises concerns for all circles in the campus environment. Unfortunately, most of the student victims are unaware that they are getting sexual harassment, especially verbally. One form of verbal abuse is sexist humor. This study aimed to find about what makes sexist humor a form of sexual violence and what we can do to prevent and control it at UIN Raden Fatah Palembang. This study used a qualitative research method. In collecting the data, a quantitative method was used by distributing the questionnaires, and qualitatively, by conducting in-depth interviews. The theory used was the theory of Communication Privacy Management (CPM). The findings and results of this study concluded that this sexist humor will continue to occur if there is no prevention and proper handling on campus, mainly because there are no institutions that can act as bridges for students to report, consult and protect victims. Another thing that is also a concern is the lack of understanding and information about sexual violence, both verbally and non-verbally, among students.